Because I’m Happy—An Overview on Fostering Positive Emotions Through Virtual Reality - Pavic , Katarina; Vergilino-Perez , Dorine; Gricourt, Thierry; Chaby, Laurence (Frontiers in Virtual Reality, 2022)
In recent years, an increased demand for improving mental health and well-being led to developing procedures capable of enhancing positive experiences. One highly attractive candidate for evoking positive experiences is Virtual Reality (VR), as VR enables users to experience various situations in controlled and safe environments. This overview first investigates how positive emotions, well-being and VR are interconnected. Then, an overview about how and why to induce positive emotions in adult users is provided. Methodological and ethical considerations about VR technology, measurements of VR’s efficacy and user characteristics are reviewed. It emerges that VR is efficient in inducing positive emotions across the adult lifespan and in various settings. Levels of immersion, interactivity, Virtual environment contents, sensory modalities involved and users’ characteristics emerged as key determinants for successfully inducing positive emotions with VR. The main applications of positive VR experiences consist in using VR for relaxation, stress and pain management, motivation for physical activities, and gives promising results for apathy treatment in elderly users. Although VR is efficient in eliciting positive emotions and experiences, the underlying operating mechanisms remain unclear and are yet to be further investigated. Finally, the need for a user-centered approach when designing positive VR experiences, clear guidelines for the use of VR, and a better documentation of its potential adverse effects are addressed.